Application of Problem Based Learning (PBL) Model to Improve Cultural Literacy Capabilities of Elementary School Students - Septiani, Devianeu Wisdiasusi; Maftuh, Bunyamin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
Indonesia is a nation which consist of a variety of traditions, tribes, and cultures. However, many Indonesian elementary school students do not know the various cultures of Indonesia. It is very important to develop cultural literacy among elementary school students, so that they will be able to understand, respect, maintain and preserve their culture. One of efforts to develop and increase cultural literacy skills of elementary school students is by implementing problem-based learning (PBL). This paper aims to explain problem-based learning (PBL) model on cultural literacy in elementary school, as an effort to encourage students develop their cultural literacy